√(2х+1) -√(х-1) =а
решить параметр

1232957 1232957    2   07.06.2021 22:29    1

Ответы
Princess358ghhh Princess358ghhh  07.07.2021 23:32

Відповідь:

ає(-inf; -√3/2]U[√3/2;+inf)

Покрокове пояснення:

√(2х+1) -√(х-1) =а

ОДЗ: 2х+1>=0 & х-1>=0 → х>=1

√(2х+1)=a+√(х-1)

2x+1=a^2+2a√(х-1)+x-1

x+2-a^2=2а√(х-1)

x^2+4x+4-2a^2(x+2)+a^4=4а^2(x-1)

x^2+4x+4-2a^2(x+2)+a^4-4а^2(x-1)=0

x^2+4x+4-2a^2x-4a^2+a^4-4а^2x+4a^2=0

x^2+2(2-3a^2) x+4+a^4=0

D=4-12a^2+9a^4-4-a^4>=0

8a^4-12a^2>=0

4a^2(2a^2-3)>=0

a^2>=3/2

|a|>=√3/2

ає(-inf; -√3/2]U[√3/2;+inf)

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика